Ultrasensitive phototransistor based on K-enriched MoO3 single nanowires - Lu, Junpeng (2013)
An ultrasensitive phototransistor was fabricated based on K-intercalated MoO3 single nanowire. Devices with ultrafast photoresponse rate, high responsivity, and broad spectral response range were demonstrated. Detailed analysis of the charge transport in the device revealed the coexistence of both thermal-activation and photoactivation mechanisms. The promising results are expected to promote the potential of this material in nano/micro-scaled photoelectronic applications.